Reclaiming Klungkung's Cultural Heritage: Navigating the Complexities of Repatriation in Post-Colonial Bali - Westerlaken, Rodney (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This article examines the complexities of repatriating objects from Bali's Klungkung Court seized by Dutch forces in 1908. It argues that repatriation, often conducted as restitution between nations, fails to fully consider local communities' needs. Through a case study of five artifacts, the article explores historical, cultural, and ethical dimensions, highlighting repatriation challenges. It emphasizes engaging local stakeholders for an equitable process. Returning these artifacts can rectify historical injustices, uphold cultural sovereignty, and foster reconciliation between the Netherlands and Indonesia, despite challenges like provenance research and ownership disputes. Repatriation remains vital for addressing colonial legacies and promoting cultural justice by acknowledging wrongs, aiding healing, empowering descendants, and sustaining cultural practices. The study concludes that repatriation is a continual, complex process requiring commitment to justice, reconciliation, and cultural autonomy, focusing on the perspectives of communities from which objects were taken.